Cholangiocarcinoma landscape in Europe: Diagnostic, prognostic and therapeutic insights from the ENSCCA Registry - Izquierdo-Sanchez, Laura; Lamarca, Angela; La Casta, Adelaida; Buettner, Stefan; Utpatel, Kirsten; Klümpen, Heinz-Josef; Adeva, Jorge; Vogel, Arndt; Lleo, Ana; Fabris, Luca; Ponz-Sarvise, Mariano; Brustia, Raffaele; et al. (Journal of hepatology, 2022)
Cholangiocarcinoma (CCA) is a rare and heterogeneous biliary cancer, whose incidence and related mortality is increasing. This study investigates the clinical course of CCA and subtypes (intrahepatic [iCCA], perihilar [pCCA], and distal [dCCA]) in a pan-European cohort. The ENSCCA Registry is a multicenter observational study. Patients were included if they had a histologically proven diagnosis of CCA between 2010-2019. Demographic, histomorphological, biochemical, and clinical studies were performed. Overall, 2,234 patients were enrolled (male/female=1.29). iCCA (n = 1,243) was associated with overweight/obesity and chronic liver diseases involving cirrhosis and/or viral hepatitis; pCCA (n = 592) with primary sclerosing cholangitis; and dCCA (n = 399) with choledocholithiasis. At diagnosis, 42.2% of patients had local disease, 29.4% locally advanced disease (LAD), and 28.4% metastatic disease (MD). Serum CEA and CA19-9 showed low diagnostic sensitivity, but their concomitant elevation was associated with increased risk of presenting with LAD (odds ratio 2.16; 95% CI 1.43-3.27) or MD (odds ratio 5.88; 95% CI 3.69-9.25). Patients undergoing resection (50.3%) had the best outcomes, particularly with negative-resection margin (R0) (median overall survival [mOS] = 45.1 months); however, margin involvement (R1) (hazard ratio 1.92; 95% CI 1.53-2.41; mOS = 24.7 months) and lymph node invasion (hazard ratio 2.13; 95% CI 1.55-2.94; mOS = 23.3 months) compromised prognosis. Among patients with unresectable disease (49.6%), the mOS was 10.6 months for those receiving active palliative therapies, mostly chemotherapy (26.2%), and 4.0 months for those receiving best supportive care (20.6%). iCCAs were associated with worse outcomes than p/dCCAs. ECOG performance status, MD and CA19-9 were independent prognostic factors. CCA is frequently diagnosed at an advanced stage, a proportion of patients fail to receive cancer-specific therapies, and prognosis remains dismal. Identification of preventable risk factors and implementation of surveillance in high-risk populations are required to decrease cancer-related mortality. This is, to date, the largest international (pan-European: 26 hospitals and 11 countries) observational study, in which the course of cholangiocarcinoma has been investigated, comparing the 3 subtypes based on the latest International Classification of Diseases 11th Edition (ICD-11) (i.e., intrahepatic [2C12], perihilar [2C18], or distal [2C15] affected bile ducts), which come into effect in 2022. General and tumor-type specific features at diagnosis, risk factors, biomarker accuracy, as well as patient management and outcomes, are presented and compared, outlining the current clinical state of cholangiocarcinoma in Europe. [Display omitted] •CCA subtypes present different risk factors and tumor features.•CA19-9 shows low sensitivity in early stages but increased sensitivity in advanced disease.•Under surgery, positive margins and lymph node invasion compromise survival.•ECOG-PS, disease status and CA19-9 are independent prognostic factors.